An Analysis of Teacher’s Strategies in Teaching Reading Comprehension - Yesicha Audina; Nibenia Zega; Asima Simarmata; Kiki Velina Situmeang; Sri Ninta Tarigan (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2020)
This study was raised due to problems in learning reading. The researchers saw that teachers and students experience constraints in the learning process. The problem is when students do not understand the content of the reading because students only learn to translate word by word and do not understand the contents of the reading. The purpose of research is to know the strategies used by English teachers and the reasons why did the English teacher choose those strategies to teach English reading comprehension and describe the application using the strategies chosen by English teachers in reading understanding learning. This research is used with research objects of English teachers. The location of this research was at SMK Dharma Bakti 1, Medan. The method of the research was qualitative research. The Instruments of this research were observations and interviews. The results of this study using the strategy of Directed Reading Activity (DRA). DRA is a strategy used to expand and strengthen students’ reading skills. In short this strategy guides students to get information from a text read. So that in its implementation students can more easily understand the text of connecting the various student knowledge that students have. Before it was to build its own understanding and this assumption, this strategy was considered effective because it was able to build a teaching learning process. Making classes more conducive, students are also trained to build good cooperation, students capable of discussion and critical thinking as well as developing understanding after reading.